2014
DOI: 10.1161/circheartfailure.114.001113
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Recovery From Ischemia–Reperfusion Is Compromised in the Absence of Tissue Inhibitor of Metalloproteinase 4

Abstract: Background-Myocardial reperfusion after ischemia (I/R), although an effective approach in rescuing the ischemic myocardium, can itself trigger several adverse effects including aberrant remodeling of the myocardium and its extracellular matrix. Tissue inhibitor of metalloproteinases (TIMPs) protect the extracellular matrix against excess degradation by matrix metalloproteinases (MMPs). TIMP4 levels are reduced in myocardial infarction; however, its causal role in progression of post-I/R injury has not been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…However, there is also evidence that it may do the opposite, namely decrease fibrosis (Takawale et al, 2014). In the present study, Timp4 was downregulated by both doses of CNT-1 and the highest dose of CNT-2 and asbestos.…”
Section: Discussionsupporting
confidence: 48%
“…However, there is also evidence that it may do the opposite, namely decrease fibrosis (Takawale et al, 2014). In the present study, Timp4 was downregulated by both doses of CNT-1 and the highest dose of CNT-2 and asbestos.…”
Section: Discussionsupporting
confidence: 48%
“…Following myocardial ischemia/reperfusion, ECM remodeling often occurs with an initial fibrotic response followed by ECM turnover. In mice lacking TIMP4, interstitial fibrosis was enhanced one week following injury compared to wild type mice [67]. Interestingly, this augmented fibrosis was associated with greater MMP14 activity as well as increased inflammation, suggesting that TIMP4 regulates ECM deposition through inhibition of MMP14 and restriction of inflammation [67].…”
Section: Indirect Regulation Of Ecm Turnover By Timp4mentioning
confidence: 99%
“…Structural remodeling of the extracellular matrix is an important contributor to abnormal ventricular TIMP4 inhibits MMP-mediated degradation of excess extracellular matrix and reduces myocardial infarction in vivo in I/R mice. 17) Chaturvedi et al 18) reported that TIMP4 attenuates oxidative stress and induces the differentiation of cardiac progenitor cells into cardiomyocytes. Our data demonstrated that TIMP4 expression upon H 2 O 2 treatment (−1.85-fold) was up-regulated in cells that were also treated with AF-HF001 (1.97-fold).…”
Section: Discussionmentioning
confidence: 99%